Using photocaging for fast time‐resolved structural biology studies. Issue 10 (4th October 2021) - Monteiro, Diana C. F.; Amoah, Emmanuel; Rogers, Cromarte; Pearson, Arwen R.
Abstract : This review summarizes the best characterized and most relevant photocaging groups for time‐resolved structural biology described in the literature to date. It provides a walkthrough of the essential factors to consider in designing a suitable photocaged molecule to address specific biological questions using time‐resolved X‐ray diffraction or solution‐scattering methods. Abstract : Careful selection of photocaging approaches is critical to achieve fast and well synchronized reaction initiation and perform successful time‐resolved structural biology experiments. This review summarizes the best characterized and most relevant photocaging groups previously described in the literature. It also provides a walkthrough of the essential factors to consider in designing a suitable photocaged molecule to address specific biological questions, focusing on photocaging groups with well characterized spectroscopic properties. The relationships between decay rates ( k in s −1 ), quantum yields (ϕ) and molar extinction coefficients (ϵmax in M −1 cm −1 ) are highlighted for different groups. The effects of the nature of the photocaged group on these properties is also discussed. Four main photocaging scaffolds are presented in detail, o ‐nitrobenzyls, p ‐hydroxyphenyls, coumarinyls and nitrodibenzofuranyls, along with three examples of the use of this technology. Furthermore, a subset of specialty photocages are highlighted: photoacids, molecular photoswitches and metal‐containing photocages. These extend the range of photocaging approaches by, for example, controlling pH or generating conformationally locked molecules.